Molecular cloning, functional analysis of three cinnamyl alcohol dehydrogenase (CAD) genes in the leaves of tea plant, Camellia sinensis - Deng, Wei-Wei; Zhang, Ming; Wu, Jian-Qiang; Jiang, Zheng-Zhong; Tang, Lei; Li, Ye-Yun; Wei, Chao-Ling; Jiang, Chang-Jun; Wan, Xiao-Chun (Journal of plant physiology, 2013)
Cinnamyl alcohol dehydrogenase (CAD; EC 1.1.1.195) is considered to be a key enzyme in lignin biosynthesis, but little was known about CADs in tea plants (Camellia sinensis). A full-length cDNA sequence (CsCAD2) was isolated by suppressive subtractive hybridization (SSH) in Ectropis oblique feeding-induced tea plants, and another two full-length cDNA sequences (CsCAD1 and CsCAD3) were obtained from a transcriptome obtained by deep sequencing. However, they showed only 20–54% identities. Phylogenetic analysis revealed that they belonged to three different families. DNA gel blotting analysis revealed that two copies of CsCAD1 and CsCAD2 genes existed in tea genome, but CsCAD3 likely had only one copy. Recombinant proteins of these CsCADs were produced in Escherichia coli. The activity of purified recombinant CsCAD2 protein was up to 0.43μmolmin−1mg−1. However, the other two recombinant proteins had lower activities, probably due to incomplete refolding. qRT-PCR analysis indicated that while CsCAD3 was strongly up-regulated in tea plants after E. oblique attack and mechanical damage, CsCAD1 and CsCAD2 showed only moderate or no changes in transcript levels. Treatment of defence-related hormones methyl jasmonate (MeJA) and salicylic acid (SA) elevated the expression of CsCAD1 and CsCAD2, but decreased the transcript abundance of CsCAD3. The transcript levels of CsCAD2 did not change after applying abscisic acid (ABA), whereas CsCAD1 and CsCAD3 were induced. These results suggested that these three CsCAD genes in tea plants may play a role in defense against insects and pathogens and adaptation to abiotic stresses and these genes likely have divergant functions.